2017
DOI: 10.1111/dme.13450
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of alirocumab in people with prediabetes vs those with normoglycaemia at baseline: a pooled analysis of 10 phase III ODYSSEY clinical trials

Abstract: AimTo assess the lipid‐lowering efficacy and safety of alirocumab, a proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, in people with hypercholesterolaemia and prediabetes at baseline vs people with normoglycaemia at baseline in a pooled analysis of 10 ODYSSEY phase III trials.MethodsPeople classified as having prediabetes had baseline HbA1c ≥39 mmol/mol (5.7%) and <48 mmol/mol (6.5%), or two baseline fasting plasma glucose values ≥5.6 mmol/l (100 mg/dl) but no more than one fasting plasma gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
(87 reference statements)
6
26
0
1
Order By: Relevance
“…In this analysis of patients with existing DM, treatment with alirocumab had no effect on FPG or HbA1c levels compared with placebo over 78 weeks of treatment and compared with ezetimibe over 104 weeks of follow‐up, including comparison of individuals receiving insulin vs those not receiving insulin. These findings are consistent with those of the ODYSSEY DM‐INSULIN trial27 and previous sub‐analyses that revealed no effect of alirocumab on glycaemic parameters31, 33, 45 or no increase in new‐onset DM compared with controls 45. Furthermore, in a recent meta‐analysis of 15 randomized controlled trials with PCSK9 inhibitors, including alirocumab, there was no increase in glycaemic parameters in those without DM or pre‐existing DM (crude rate, 5.6% vs 5.9%; odds ratio, 1.05 [95% confidence interval, 0.95‐1.17], P = .32, I2 = 0%, heterogeneity P = .86) 46.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this analysis of patients with existing DM, treatment with alirocumab had no effect on FPG or HbA1c levels compared with placebo over 78 weeks of treatment and compared with ezetimibe over 104 weeks of follow‐up, including comparison of individuals receiving insulin vs those not receiving insulin. These findings are consistent with those of the ODYSSEY DM‐INSULIN trial27 and previous sub‐analyses that revealed no effect of alirocumab on glycaemic parameters31, 33, 45 or no increase in new‐onset DM compared with controls 45. Furthermore, in a recent meta‐analysis of 15 randomized controlled trials with PCSK9 inhibitors, including alirocumab, there was no increase in glycaemic parameters in those without DM or pre‐existing DM (crude rate, 5.6% vs 5.9%; odds ratio, 1.05 [95% confidence interval, 0.95‐1.17], P = .32, I2 = 0%, heterogeneity P = .86) 46.…”
Section: Discussionsupporting
confidence: 92%
“…Alirocumab has also been demonstrated to reduce major adverse cardiovascular events vs placebo in patients with recent acute coronary syndrome in the ODYSSEY OUTCOMES trial 29. Subgroup analyses have suggested similar efficacy and tolerability of alirocumab in individuals with and without DM 26, 30, 31, 32, 33. However, it is important to examine the effects of alirocumab in the specific subgroup of individuals with both DM and ASCVD who are at particularly high risk and may benefit from additional lipid‐lowering therapy beyond a statin 7, 8, 9, 10, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Findings were consistent in the prespecified diabetes mellitus subanalysis of FOURIER, which analyzed 11 031 patients with diabetes mellitus versus 16 533 patients without diabetes mellitus; compared with placebo, median LDL‐C levels were reduced by 57% in those with diabetes mellitus and by 60% in those without diabetes mellitus 71. Other subanalyses of ODYSSEY and PROFICIO phase 3 trials showed that LDL‐C reductions were also similar in those with and without prediabetes,72 impaired fasting glucose, and metabolic syndrome (Table). 73 Similarly, a recent post‐hoc subanalysis of 9 ODYSSEY phase 3 trials (24–104 weeks’ treatment duration) showed significant LDL‐C reductions with alirocumab in patients with both diabetes mellitus and ASCVD (Table).…”
Section: Lipid‐lowering Efficacy Of Pcsk9 Inhibitors In Patients Withsupporting
confidence: 58%
“…Overall safety was also comparable versus control between patients with diabetes mellitus and ASCVD,68 insulin‐treated patients with diabetes mellitus in the DM‐INSULIN study,75 patients with T2D and mixed dyslipidemia in the DM‐DYSLIPIDEMIA study,77 individuals with prediabetes and normoglycemia,72 and those with and without dysglycemia or metabolic syndrome 73. As shown in prior studies in the overall patient population,63, 78 higher rates of local injection‐site reactions (also generally mild) were typically seen with alirocumab/evolocumab compared with control for patients both with and without diabetes mellitus 69, 71, 80.…”
Section: Safety Of Pcsk9 Inhibitors In Patients With Diabetes Mellitumentioning
confidence: 91%
See 1 more Smart Citation